Evolution of the energy service : real necessity or solution for the development and accessibility of electricity in Africa : the case of Djibouti - (:unkn) unknown (My University, 2018)
In a global context marked by a growth of energy demands, particularly in sub-Saharan Africa,this thesis is devoted to the analysis of both the management and impact of energy services in Djibouti. Hence, the study describes the network of electricity distribution in Djibouti and the various organs in charge of this energy service.The government undertook organizational innovation by implementing interconnection with a view of diversifying its production sources, lessening its vulnerability and ultimately reducing people’s energy bill.This is the reason why the study tackles the question of innovation in the energy sector through a quantitative survey on household, with a focus on residential sector in Djibouti. Semi-structured interviews were also conducted the in the hotel sector.Findings show that interconnection proved unfruitful, that is to say that energy bill has not been reduced in both residential and non-residential sector; however, it helped reducing load shedding, which, in turn, resulted in a slight improvement of the quality of the service.
Keywords: African Research